UTILIZATION OF SORGHUM FLOUR SUBSTITUTION IN CHICKEN RENDANG GYOZA SKIN - Siti Hamidah, Shafia Aqla Dzakia (Prosiding Pendidikan Teknik Boga Busana, 2020)
Excess sorghum as food, feed, and the industry is rich in functional food component. The diversity of antioxidants, mineral elements, especially Fe, fiber, oligosaccharides, and b-glucan including carbohydrate component nonstarch polysakarida (NSP) contained in grain sorghum making potential as a source of functional food. The uniqueness of the sorghum is the presence of tannins and phytic acid which raised controversy negative and positive impact on health. Tannins higher antioxidant properties than vitamins E and C, as well as sorghum more stable anthocyanin antioxidants. This is the main attraction. The purpose of this study was to find a recipe substitution of sorghum flour with wheat flour for rendang chicken gyoza skin and determine the level of public acceptance of rendang chicken gyoza dish of these materials. The method used is a type of Research and Development with the concept of 4D. Dianalsis data obtained were analyzed by three methods: qualitative descriptive analysis, the chart data and percentages. Based on the research society acceptance level of the color, flavor, aroma and texture of the product gyogum (gyoza sorghum rendang chicken) was excellent. Keywords: Sorghum, analysis, wheat flour,